Promoting Innovation Ecosystem from Knowledge Supplying Side - WANG, Yuqiu (Management Dynamics in the Knowledge Economy, 2017)
Innovation and development paradigm has dominated the world since the 19th century. In the era of industry 4.0, innovation ecosystem has been advocated globally. There are different innovation paradigms in history. Before 1960s, the competitive and monopolized paradigm was dominative, while between the 1970s and 1990s, the cluster and innovation valley paradigm had played a key role. In the 21st century, with the advent of industry 4.0, the innovation ecosystem paradigm is advocated globally. Accordingly, there exist different innovation strategies, in reality, considering different economic and social context. However, no matter if having in mind developed or developing countries, the ecosystem paradigm has high rewards for different companies and society. There is also evidence showing that research and development by top universities and research institutes have high productivity and benefits for enterprises and society nowadays, no matter the development state of the areas considered. The author analyzes by literature review and case study the necessity, feasibility, strategy and approaches of innovation ecosystem from a knowledge supplying side. The strategy and approaches include collaboration between university, industry, agriculture and government, talents education, knowledge diffusion, patent purchasing, technology tailoring, consulting, human resource training and platform construction. Science community also takes the role of standards development and maintaining, high technology forecasting and innovation monitoring. The patent office, start-ups, spin-offs and innovation labs act as the links between science, technology, and application.